Pengembangan Lembar Kerja Siswa (LKS) Menggunakan Ikon Kota Lubuklinggau - Yana Royana; Idul Adha; Rani Refianti (Jurnal Pendidikan Matematika:Judika Education, 2019)
This study aims to develop Student Worksheets (LKS) using the icon of the City of Lubuklinggau (Great Mosque of the As-Salam Taman Kurma) on valid and practical class X trigonometry material. The research method used is the research method of development, Research and Depelopment (R&D) which has been modified into 3-D which in this study uses 3 stages, namely the stage of definition (Define), design, (Design) and development (Develop). Worksheets developed in the level of validity were seen from the expert questionnaire, while practicality was measured from the practicality questionnaire for students. The results of the study, from the analysis of the assessment of four experts namely linguists, material experts, content experts, and media experts showed that the worksheet met valid criteria with an average score of 3.18. While the results of the analysis of the LKS assessment on field trials of students meet practical criteria with an average score of 3.15. In conclusion, the worksheets are designed using the icon of the city of Lubuklinggau with valid and practical trigonometry material Keyword: City Icons, LKS Development